Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents] - L.M.F. Purwanto (Universitas Katolik Soegijapranata, 2022)
Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents]